Geopolymer as well as preparation method and application thereof
By mixing fly ash, alkaline activator and water in a specific proportion, and performing geological polymerization under conditions of 100°C to 300°C, the problem of long preparation of fly ash aggregate and easy cracking at high temperatures is solved. High hardness geological polymer preparation is achieved, suitable for the replacement of building materials.
Patent Information
- Application Number
- CN202311019375.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-21
AI Technical Summary
In the prior art, fly ash takes a long time in the preparation of aggregates and cannot be geologically polymerized at high temperatures, resulting in high moisture content and easy cracking of the product.
By mixing fly ash, alkaline activator and water at a mass ratio of 80 to 99.75:0.25 to 20, geological polymerization of 100°C to 300°C is carried out. Through pre-drying and forming and curing steps, the geological polymerization time is shortened and energy is reduced. Consumption.
It achieves high hardness (22MPa~25MPa) of geological polymers, and has a short production cycle and is easy to apply. It can replace precast concrete, sand and traditional building stone, and is suitable for the preparation of aggregates and building components.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of building materials, and in particular to geopolymers and a preparation method and application thereof. Background Art
[0002] At present, fly ash waste is often disposed of by landfill, which causes serious environmental pollution, generates dust that enters the air, and occupies land for landfill. On the other hand, building materials such as sand and stone are becoming increasingly scarce because they are non-renewable resources. With the growth of population, the demand for construction and building materials production is also increasing. However, fly ash is still limited in its application in the construction field due to its ultra-fine and lightweight characteristics.
[0003] Related art discloses a method for making aggregate using fly ash. This method takes a long time in the preparation of aggregate, resulting in high energy consumption (mainly because: this method takes a long time to transfer heat from the surface of the product to the inside of the product); and the fly ash granulation method is as follows: surface treatment is performed by spray drying to obtain fine-grained fly ash; the fine-grained fly ash can be used to replace construction sand. The fine-grained fly ash artificial sand has a low modulus and low hardness, and is only suitable for construction sand in certain specific situations (that is, the fly ash cannot be used as a raw material under normal circumstances); and the production capacity of the granulation method is also difficult to increase.
[0004] That is, the method of utilizing fly ash in the related art is time-consuming and cannot be geopolymerized at high temperatures (the product has a high moisture content and is prone to cracking during high-temperature geopolymerization). Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a geopolymer in view of the deficiencies in the prior art, so as to solve the problem that the geopolymer is easy to crack in the related art.
[0006] The present invention provides a geopolymer prepared by the above method.
[0007] The present invention also provides application of the geopolymer.
[0008] The present invention provides a method for preparing a geopolymer, comprising the following steps:
[0009] Geopolymerizing the geopolymer mortar at 100°C to 300°C;
[0010] The raw materials for preparing the geopolymer mortar include:
[0011] fly ash, alkaline activator and water;
[0012] The mass ratio of the fly ash to the alkaline activator is 80-99.75:0.25-20.
[0013] According to one technical solution of the preparation method technical solution of the present invention, at least the following beneficial effects are achieved:
[0014] The present invention provides a method for preparing geopolymers, which is a method for drying products "after forming" for geopolymerization of products to achieve maximum hardness of the products.
[0015] The geopolymer prepared by the method can replace precast concrete, sand and traditional building stones. The method of the invention has a short production cycle and is easy to apply in production practice; the method of the invention can produce specific products according to actual needs; thus, the products can be applied to the preparation of aggregates and building components.
[0016] According to some embodiments of the present invention, the mass fraction of water in the geopolymer mortar is 6% to 30%.
[0017] According to some embodiments of the present invention, the raw materials for preparing the geopolymer further include at least one of sand, stone, gravel and reinforcing fiber.
[0018] According to some embodiments of the present invention, the raw material for preparing the geopolymer further includes a tetrapod block.
[0019] According to some embodiments of the invention, the geopolymerization comprises the following steps:
[0020] S1, heating the geopolymer mortar to 100° C. to 150° C. and pre-drying it to obtain a pre-dried mortar;
[0021] S2, heating the pre-dried mortar obtained in step S1 to 100° C. to 300° C. to obtain a molded mortar;
[0022] S3, further curing the formed mortar obtained in step S2 at 100°C to 300°C.
[0023] During the mortar product molding process, the temperature of the mold used to mold the product is above the geopolymerization temperature, thereby shortening the geopolymerization time and reducing the heat consumed by geopolymerization, thereby greatly reducing the production cost of geopolymers.
[0024] In addition, according to the theory of geopolymer technology, the temperature of geopolymerization starts from 60°C, so the pre-drying method of geopolymer mortar proposed in the present invention (heating to 100°C to 120°C for pre-drying) will be a brand-new method.
[0025] According to some embodiments of the present invention, the pre-drying method in step S1 is a conventional drying method.
[0026] According to some embodiments of the present invention, the pre-drying method in step S1 is combined drying.
[0027] According to some embodiments of the present invention, the combined drying process consists of a first drying process and a second drying process.
[0028] According to some embodiments of the invention, the first drying method is conveyor drying.
[0029] According to some embodiments of the present invention, the second drying method includes at least one of hot air drying, steam drying, infrared drying, microwave drying and near infrared drying.
[0030] Hot air drying: Use hot air to transfer heat to the material. Hot air is generated by burning fuel (such as oil, gas, coal) or using other heat sources (such as thermal power, steam) to heat the air and then introduce it into the drying process.
[0031] Steam Drying: uses steam to provide heat. Steam is produced by boiling water or using a steam system. Steam is introduced into the drying process and transfers heat to the material, which then evaporates the water in the material.
[0032] Infrared Drying: Uses infrared light to transfer heat to the material. The infrared light can be emitted from a heat source (such as an infrared bulb) and acts on the surface and heats the material.
[0033] Microwave drying: Use microwaves to transfer energy and increase the temperature of the material. Microwaves act on the water molecules in the material and heat the material.
[0034] Near infrared drying: uses near infrared light to transfer heat to the material. Near infrared light has a longer wavelength than regular infrared light, so it can penetrate the material more deeply, resulting in better drying effects.
[0035] According to some embodiments of the present invention, the pre-drying time in step S1 is 10 min to 15 min.
[0036] According to some embodiments of the present invention, in step S2, the pre-dried mortar is heated in a mold, a roller or a rolling plate.
[0037] According to some embodiments of the present invention, in step S2, the mold, roller or rolling plate is exposed to a heat source for heating.
[0038] According to some embodiments of the present invention, the heat source is at least one of hot air, electrical resistance, hot water, hot oil, high temperature gas and steam.
[0039] During the rolling process of the fly ash particles, heat is transferred from the roller surface through the outer surface of the fly ash particles, thereby heating the entire volume or a portion of the fly ash particles (if the fly ash particles are large).
[0040] According to some embodiments of the present invention, the heating temperature in step S2 is 150°C to 200°C.
[0041] According to some embodiments of the present invention, the heating time in step S2 is 5 min to 10 min.
[0042] According to some embodiments of the present invention, the further curing time in step S3 is 1 min to 5 min.
[0043] According to some embodiments of the invention, the geopolymerization comprises the following steps:
[0044] S01, heating the geopolymer mortar to 100°C to 300°C to form a formed mortar;
[0045] S02, further curing the formed mortar obtained in step S01 at 100° C. to 300° C.
[0046] The combination of step S01 and step S02 is generally suitable for products with a smaller thickness, and heat can be easily transferred from the molding die to the entire volume of the product.
[0047] According to some embodiments of the present invention, in step S01, the forming is heated in the mold, roller or rolling plate.
[0048] According to some embodiments of the present invention, in step S01 , the mold, the roller or the rolling plate is exposed to a heat source for heating.
[0049] According to some embodiments of the present invention, the heating temperature in step S01 is 150°C to 200°C.
[0050] According to some embodiments of the present invention, the heating time in step S01 is 5 min to 10 min.
[0051] According to some embodiments of the present invention, the further curing time in step S02 is 1 min to 5 min.
[0052] According to some embodiments of the invention, the geopolymerization comprises the following steps:
[0053] S001, pre-drying the geopolymer mortar after heating it to 100°C to 150°C to obtain pre-dried mortar;
[0054] S002, heating the pre-dried mortar obtained in step S001 to 100°C to 300°C for shaping and curing.
[0055] Step S001 and step S002 provide sufficient heat to geopolymerize the product, and further curing is omitted.
[0056] According to some embodiments of the present invention, the pre-drying time in step S001 is 10 min to 15 min.
[0057] According to some embodiments of the present invention, in step S002, the pre-dried mortar is heated in a mold, a roller or a rolling plate.
[0058] According to some embodiments of the present invention, in step S002, the mold, the roller or the rolling plate is exposed to a heat source for heating.
[0059] According to some embodiments of the present invention, the heating temperature in step S002 is 150°C to 200°C.
[0060] According to some embodiments of the present invention, the heating time in step S002 is 5 min to 10 min.
[0061] According to some embodiments of the invention, the geopolymerization comprises the following steps:
[0062] S0001. Pre-drying the geopolymer mortar after heating it to 100° C. to 150° C. to obtain pre-dried mortar;
[0063] S0002. Heat the pre-dried mortar obtained in step S0001 to 100° C. to 300° C. for further curing.
[0064] The combination of step S0001 and step S0002 is usually suitable for products with thicker thickness, where heat has been supplied to the entire volume of the product and is close to reaching the geopolymerization temperature.
[0065] According to some embodiments of the present invention, the pre-drying time in step S0001 is 10 min to 15 min.
[0066] According to some embodiments of the present invention, the further curing time in step S002 is 1 min to 5 min.
[0067] According to some embodiments of the present invention, the time of the geopolymerization is 10 min to 60 min.
[0068] According to some embodiments of the present invention, the ignition loss of the fly ash is 12% to 13%.
[0069] According to some embodiments of the present invention, the mass fraction of SiO2 in the fly ash is 50% to 55%.
[0070] According to some embodiments of the present invention, the mass fraction of Al2O3 in the fly ash is 20% to 25%.
[0071] According to some embodiments of the present invention, the mass fraction of Fe2O3 in the fly ash is 5% to 10%.
[0072] According to some embodiments of the present invention, the mass fraction of CaO in the fly ash is 0.5% to 1%.
[0073] According to some embodiments of the present invention, the particles larger than 45 μm in the fly ash account for 35% to 40%.
[0074] According to some embodiments of the invention, the alkaline activator comprises at least one of sodium hydroxide and potassium hydroxide.
[0075] The present invention controls the temperature of the geopolymer mortar to be close to the geopolymerization temperature (maximum 300° C.); and the critical temperature of NaOH or KOH in the alkaline activator is above 300° C., that is, the alkaline activator still has a certain activity at the geopolymerization temperature.
[0076] The second aspect of the present invention provides a geopolymer prepared by the above-mentioned preparation method.
[0077] According to some embodiments of the present invention, the hardness of the geopolymer is 22 MPa to 25 MPa.
[0078] The third aspect of the present invention provides the use of the above geopolymer in preparing aggregates and / or building components.
[0079] According to some embodiments of the present invention, the geopolymer is ground to produce building sand.
[0080] According to some embodiments of the present invention, the particle size of the building sand is 2 mm to 3 mm. DETAILED DESCRIPTION
[0081] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0082] Obviously, the embodiments described below are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios based on these embodiments without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in this field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as the content disclosed in this application is insufficient.
[0083] Reference to "embodiments" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those of ordinary skill in the art that the embodiments described in this application may be combined with other embodiments without conflict.
[0084] Unless otherwise defined, the technical terms or scientific terms involved in this application should be understood by people with ordinary skills in the technical field to which this application belongs. The words "one", "a", "a", "the" and the like involved in this application do not indicate a quantitative limitation, and may represent the singular or plural. The terms "include", "comprise", "have" and any of their variations involved in this application are intended to cover non-exclusive inclusions; for example, a process, method, system, product or device that includes a series of steps or units (units) is not limited to the listed steps or units, but may also include steps or units that are not listed, or may also include other steps or units inherent to these processes, methods, products or devices. The words "connect", "connected", "coupled" and the like involved in this application are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. The "multiple" / "several" involved in this application refers to two or more. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, "A and / or B" can mean: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the objects before and after are in an "or" relationship. The terms "first", "second", "third", etc. involved in this application are only used to distinguish similar objects and do not represent a specific ordering of the objects.
[0085] The percentages of some raw materials in the fly ash used in the embodiment of the present invention are shown in Table 1.
[0086] Table 1 Percentage content of some raw materials in fly ash
[0087] - Loss on ignition <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO Particles larger than 45 μm Mass fraction (%) 12.8 52.6 21.3 5.31 0.88 36.1
[0088] Example 1
[0089] This embodiment is a method for preparing a geopolymer, which consists of the following steps:
[0090] S1, drying the geopolymer mortar in a rotary kiln for 15 min to obtain pre-dried geopolymer mortar (temperature is 130°C ± 10°C);
[0091] S2. The pre-dried geopolymer mortar prepared in step S1 is sent to a briquetting machine for molding (there are two rollers in the briquetting machine; the temperature of the rollers is 155°C ± 5°C, the molding shaft rotates continuously during the molding process, and the heating time of the material is extremely short (about 1s)) to obtain a molded product (the size of the molded product is oval, the size is 60mm×30mm, and the thickness is 25mm).
[0092] S3, placing the molded product in step S2 into a microwave oven, heating the entire roll to 165°C±5°C for 5 minutes, and obtaining a geopolymer.
[0093] The raw materials for preparing geopolymers in this step consist of the following raw materials of quality:
[0094] 990kg fly ash, 10kg alkaline activator (sodium hydroxide) and 100kg water.
[0095] The preparation method of the geopolymer in this step consists of the following steps:
[0096] mixing an alkaline activator and water to prepare an alkaline solution;
[0097] The fly ash and alkaline solution are then mixed, stirred and roller pressed.
[0098] The hardness of the geopolymer prepared in this embodiment is 25 MPa (obtained by Rockwell hardness tester).
[0099] The geopolymer in this example is used to prepare building sand.
[0100] The preparation method of building sand in this embodiment is:
[0101] The geopolymer was ground to a particle size of 2 mm to 3 mm.
[0102] In this embodiment, 1000 kg of building sand is obtained.
[0103] Example 2
[0104] This embodiment is a method for preparing a geopolymer, which consists of the following steps:
[0105] S1. Send the geopolymer mortar grouting into the roller mill for molding (there are 2 rollers in the roller mill (coal briquette machine); the temperature of the roller is 180°C) to obtain a molded product (the size of the molded product is oval, the size is 60mm×30mm, the thickness is 10mm, the molding shaft rotates continuously during the molding process, and the heating time of the material is extremely short (about 1s)).
[0106] S2, polymerizing the molded product in step S1 at 160° C. (due to heat transfer on the roller surface, the temperature of the molded product reaches 160° C.); obtaining a geopolymer.
[0107] The raw materials for preparing geopolymers in this step consist of the following raw materials of quality:
[0108] 990kg fly ash, 10kg alkaline activator (sodium hydroxide) and 100kg water.
[0109] The preparation method of the geopolymer in this step consists of the following steps:
[0110] mixing an alkaline activator and water to prepare an alkaline solution;
[0111] The fly ash and alkaline solution are then mixed, stirred and roller pressed.
[0112] The hardness of the geopolymer prepared in this embodiment is 24 MPa.
[0113] The geopolymer in this example is used to prepare building sand.
[0114] The preparation method of building sand in this embodiment is:
[0115] The geopolymer was ground to a particle size of 2 mm to 3 mm.
[0116] In this embodiment, 1000 kg of building sand is obtained.
[0117] Example 3
[0118] This embodiment is a method for preparing a geopolymer, which consists of the following steps:
[0119] S1. Dry the geopolymer mortar in a rotary kiln for 15 min to obtain pre-dried geopolymer mortar (temperature is 145°C ± 5°C);
[0120] S2, the pre-dried geopolymer mortar prepared in step S1 is grouted into a Tetrapod mold for molding (the Tetrapod mold is assembled from many steel plates, which can be separated to obtain the product after molding; the Tetrapod mold is placed on a vibration plate for mechanical vibration to fill the mold with the pre-dried geopolymer mortar, and the molding time is 10 minutes), to obtain a molded product.
[0121] S3, placing the molded product in step S2 into an oven, heating to 165°C±5°C for 30 minutes, and obtaining a geopolymer.
[0122] The raw materials for preparing geopolymers in this step consist of the following raw materials of quality:
[0123] 990kg fly ash, 10kg alkaline activator (sodium hydroxide) and 100kg water.
[0124] The preparation method of the geopolymer in this step consists of the following steps:
[0125] mixing an alkaline activator and water to prepare an alkaline solution;
[0126] The fly ash and alkaline solution are then mixed, stirred and roller pressed.
[0127] The hardness of the geopolymer prepared in this embodiment is 23 MPa.
[0128] In summary, the present invention provides a method for preparing geopolymers, and the geopolymers prepared by the method can replace precast concrete, sand and traditional building stones. The method of the present invention has a short production cycle and is easy to apply in production practice; and the method of the present invention can produce specific products according to actual needs; thereby the products are applied to the preparation of aggregates and building components.
[0129] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the specification of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a geopolymer, characterized in that: The following steps are involved: Geopolymerizing the geopolymer mortar at 100°C to 300°C; The raw materials for preparing the geopolymer mortar include: fly ash, alkaline activator and water; The mass ratio of the fly ash to the alkaline activator is 80-99.75:0.25-20.
2. The preparation method according to claim 1, characterized in that: The mass fraction of water in the geopolymer mortar is 6% to 30%.
3. The preparation method according to claim 1, characterized in that: The raw materials for preparing the geopolymer also include at least one of sand, stone, gravel and reinforcing fiber.
4. The preparation method according to claim 1, characterized in that: The geopolymerization comprises the following steps: S1, heating the geopolymer mortar to 100° C. to 150° C. and pre-drying it to obtain a pre-dried mortar; S2, heating the pre-dried mortar obtained in step S1 to 100° C. to 300° C. to obtain a molded mortar; S3, further curing the formed mortar obtained in step S2 at 100°C to 300°C.
5. The preparation method according to claim 1, characterized in that: The geopolymerization comprises the following steps: S01, heating the geopolymer mortar to 100°C to 300°C to form a formed mortar; S02, further curing the formed mortar obtained in step S01 at 100° C. to 300° C.
6. The preparation method according to claim 1, characterized in that: The geopolymerization comprises the following steps: S001, pre-drying the geopolymer mortar after heating it to 100°C to 150°C to obtain pre-dried mortar; S002. Heat the pre-dried mortar obtained in step S001 to 100° C. to 300° C. for curing.
7. The preparation method according to claim 1, characterized in that: The geopolymerization comprises the following steps: S0001. Pre-drying the geopolymer mortar after heating it to 100° C. to 150° C. to obtain pre-dried mortar; S0002. Heat the pre-dried mortar obtained in step S0001 to 100° C. to 300° C. for further curing.
8. The preparation method according to claim 1, wherein the time of the geopolymerization is 10 min to 60 min.
9. Geopolymer, characterized in that Prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the geopolymer according to claim 9 in the preparation of aggregates and / or building components.
Citation Information
Patent Citations
Method for solidifying lead alkali residues by using fly ash-based geopolymer with assistance of microwaves
CN110981302A